Magnetic Field Monitoring of Four Massive A–F Supergiants - Gregg A. Wade; Mary Oksala; Coralie Neiner; Étienne Boucher; James A. Barron (The Astrophysical Journal Letters)
We report magnetic field measurements spanning about 15 yr of four massive (7.5–15 M _⊙ ) supergiant stars: α Per (HD 20902, F5Iab), α Lep (HD 36673A, F0Ib), η Leo (HD 87737, A0Ib) and 13 Mon (HD 46300, A1Ib). For each star, spectropolarimetric observations were collected using ESPaDOnS at the Canada–France–Hawaii Telescope. The observed spectra were coadded, normalized, and then processed using least-squares deconvolution to yield mean Stokes I and V profiles. Each spectrum was analyzed to infer the false-alarm probability of signal detection, and the longitudinal magnetic field was measured. This process yielded persistent detection of magnetic fields in all four stars. The median 1 σ longitudinal field uncertainty of the Zeeman detections was 0.6 G. The maximum unsigned longitudinal magnetic fields measured from the detections are rather weak, ranging from 0.34  ±  0.19 G for α Lep to 2.61  ±  0.55 G for 13 Mon. The Zeeman signatures show different levels of complexity; those of the two hotter stars are relatively simple, while those of the two cooler stars are more complex. The stars also exhibited different levels of variability of their Zeeman signatures and longitudinal fields. We report periodic variability of the longitudinal field and (complex) Stokes V profiles of α Per with a period of either 50.75 days or 90 days. The (simple) Stokes V profiles of 13 Mon, and probably those of η Leo, show global polarity changes once during the period of observation, but the data are insufficient to place strong constraints on the variability timescales.